Comparison of Efficiency 3D Rendering Methods for Augmented Reality: A Case Study of SRP, URP, and Light Estimation on a Mobile Device - Sri Suci Indasari; Achmad Zulfajri Syaharuddin; Nurhikmayana Janna; Irmawati (Program Studi Teknik Komputer, 2025)
This study examines the efficiency of 3D rendering methods in the development of Augmented Reality (AR) applications, which significantly impact visual quality, response speed, and device resource consumption. The main objective of this research is to analyze and compare three commonly used rendering methods in AR development: Standard Render Pipeline (SRP), Universal Render Pipeline (URP), and Light Estimation. Data collection was conducted through the implementation of an AR prototype application featuring two 3D objects (Earth and Mars), followed by testing the render latency for each method. The results showed that all three methods produced the same latency time of 0.03 seconds on a high-specification device. These findings suggest that, under the given testing conditions, the choice of rendering method has no significant impact on rendering latency. However, overall efficiency may still be influenced by other factors such as lighting conditions, hardware specifications, and marker quality.